Impacts of Extreme Weather Event in Southeast Brazilian Mangrove Forest - Lima, Nádia; Cunha-Lignon, Marília [UNESP]; Martins, Alécio; Armani, Gustavo; Galvani, Emerson (MDPI, 2023)
Climate oscillations are becoming more extreme, and mangroves may be more susceptible to changes in physical conditions that can lead to mass diebacks. The current study analysed the impacts of an extreme weather event in the Cananéia-Iguape Coastal System, southeast Brazilian mangroves and the condition of the area over three years. We used a multiproxy approach, including analyses of climatic attributes, structural vegetation, and vegetation indices. Damage caused by a strong storm and hail damage had a severe impact on mangrove areas. A meteorological station installed in the mangrove since 2008 recorded a maximum wind gust of 58 km·h−1 on 30 May 2019. On the Beaufort scale, this speed is classified as strong wind. After the extreme weather event, there were catastrophic impacts on the mangrove, with more than 90% dead trunks. Vegetation indices were reduced, indicating intense changes. The NDVI of the mangroves was reduced from 0.72 to 0.35. The LAI confirmed this premise, with a reduction from 4.25 to 0.63. After three years, natural recovery had not occurred. Extreme weather events have continued to occur along coasts, drastically altering the landscape. Mangroves have been affected by these events, and depending on the state of health of the forests, may have difficulties in recovery.
Keywords: climate effects; hail; monitoring; permanent plot; remote sensing; vegetation indices; vegetation structure